From Work Life to School: Theoretical Approaches for School Burnout - Zekeriya Cam; Selahiddin Ogulmus (Psikiyatride Güncel Yaklaşımlar, 2019)
The concept of burnout, which was dealt within the context of working life in the beginning, has begun to be examined by adapting it to the school environment. Burnout, defined as a decline of energy physically, emotionally and in the feelings of achievement of the work that is being done as well as a decline in the sense of personal achievement, is used similarly to describe school burnout. In recent years, it has been reported that this concept, addressed within the context of school, results in depres-sion, absenteeism, lack of connection with school and dropout. When the literature is examined, it is seen that the approaches to the concept of school burnout in the theoretical sense are mostly conserva-tion of resources theory, demands-resources model, social cognitive theory, existential perspective and developmental process model. The aim of this research to include explanations of the aforementioned theories on school burnout and based on these theories to present suggestions to the field of mental health and future researchers.